Water Quality Analysis Based on Diversity and Abundance of Plankton in the Way Besai River, North Lampung: Analisis Kualitas Air Berdasarkan Keanekaragaman dan Kelimpahan Plankton di Sungai Way Besai Lampung Utara - Nazma, Anya Khalisza Putri; Tugiyono, Tugiyono; Farisi, Salman; Susanto, Gregorius Nugroho (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2025)
Plankton is one of the aquatic biota that can act as a bioindicator of Water because it is susceptible to changes in the quality of the Water where it lives. The Way Besai River is in Dwikora Village, Bukit Kemuning District, North Lampung Regency. This study aimed to determine the water quality of the Way Besai River based on the diversity and abundance of plankton as a bioindicator of Water and to determine the relationship between the plankton community structure and water quality parameters. This study was conducted in November-December 2024. Sampling was performed using a survey method with 6 (six) spots, which were then identified and calculated using the Sedgewick-Rafter method. Based on the analysis of plankton abundance and diversity, it is known that the Way Besai River is moderately polluted, and there is a significant relationship between the plankton community structure and water quality parameters.